Optimal design for low sonic boom based on CoKriging surrogate model - ZHANG Hanqi; XU Yue; ZHONG Min; LI Yan (Hangkong gongcheng jinzhan, 2025)
Accurately predicting and effectively reducing sonic boom levels is one of the key issues in the development of the new generation of green supersonic civil aircraft. In order to improve the efficiency of low sonic boom optimal design for supersonic civil aircraft, a multi-fidelity optimal design program for low sonic boom is developed based on the CoKriging surrogate model combined with fast sonic boom prediction method and high fidelity sonic boom prediction method. The sonic boom prediction results of the TU-144 model are basically consistent with the experimental results, verifying the reliability of the two prediction methods. A parameter sensitivity analysis and optimal design are conducted on the wing shape of a certain supersonic civil aircraft model. The results show that Stevens′ loudness level of the ground sonic boom is more sensitive to three parameters:the half span length of the outer wing, leading edge sweep angle of the outer wing, the half span length of the inner wing. After optimization, the maximum ground sonic boom overpressure is reduced by about 4 Pa, and the Stevens′ loudness level is reduced by 4.26 dB. Compared with the Kriging model that only uses high fidelity sample data, the CoKriging model integrates high and low fidelity sample data, saving about 43% of time cost while ensuring a certain prediction accuracy.